Che Guevara - Il corpo e il mito . Che Guevara - The Body and the Legend - Brunetti, Raffaele (B&B Film, 2007)
Verzio FF Submission The film examines the final hours of one of history's most enigmatic figures. Che Guevara was a poster boy for revolution, having abandoned a career in medicine to join Fidel Castro's revolutionary "26th of July" movement, which seized power in Cuba in 1959, deposing the dictator Batista and, in the following decade, joining revolutions in Congo-Kinshasa and Bolivia. Described alternately as "the most complete human being of our age" and a "sociopathic thug", Guevara was transformed in death into a demigod revolutionary, his reputation and mystique enhanced by the disappearance (and subsequent return) of his body.